Thermal deformation resistant engineering plastic and air conditioner fan blade

By adding long glass fibers, nanosilica and graphene to the polyphenylene sulfide matrix, and using benimide toughening agent and crosslinking agent for modification, combined with glass fiber surface silane treatment and ultrasonic dispersion technology, the problems of insufficient strength retention rate, poor dimensional stability and high brittleness under high temperature conditions are solved, and the high-temperature performance of the material is improved.

CN119592068AInactive Publication Date: 2025-03-11GUANGZHOU THINGFU POLYMER LTD CO

Patent Information

Application Number
CN202411913930.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyphenylene sulfide composite materials have insufficient strength retention, poor dimensional stability and high brittleness under high temperature conditions, which limits their wider application.

Method used

By adding long glass fibers, nanosilica and graphene to the polyphenylene sulfide matrix, and modifying them with benimide toughening agent, crosslinking agent and antioxidant, combined with glass fiber surface silane treatment and ultrasonic dispersion technology, the melt blending process is optimized.

Benefits of technology

It significantly improves the high-temperature strength retention, dimensional stability and toughness of the material, solves the problem of insufficient performance of existing materials under high temperature conditions, and is suitable for air conditioning fan blades and other high-temperature application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592068A_ABST
    Figure CN119592068A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of engineering plastic modification, and discloses a thermal deformation resistant engineering plastic and an air conditioner fan blade, the thermal deformation resistant engineering plastic comprises the following components: 55%-60% of polyphenylene sulfide, 20%-25% of long glass fiber, 3%-5% of nano silica, 1%-2% of a graphene filler, 8%-10% of a benzimide flexibilizer, 0.5%-1% of a cross-linking agent, and 0.2%-0.5% of an antioxidant, the invention further discloses the heat-deformation-resistant air conditioner fan blade, the heat-deformation-resistant air conditioner fan blade is prepared from the heat-deformation-resistant engineering plastic, and the preparation method of the heat-deformation-resistant air conditioner fan blade comprises the steps that the engineering plastic is subjected to injection molding through an injection molding machine, the temperature of a charging barrel is set to be 290-320 DEG C, the temperature of a mold is set to be 290-320 DEG C, and the pressure maintaining time is 15-20 seconds. The silane coupling agent is adopted to perform surface modification on the glass fiber and the nano filler, so that the problems of low high-temperature strength retention rate, poor dimensional stability and high brittleness in the prior art are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastic modification, in particular to a heat-deformation-resistant engineering plastic and an air-conditioning fan blade. Background Art

[0002] With the growing demand for high-performance materials in the industrial field, heat-resistant engineering plastics are increasingly used in the automotive, electrical and electronic, and home appliance fields. Among them, composite materials based on polyphenylene sulfide have become an important choice for use in high-temperature environments due to their excellent heat resistance and chemical stability. However, the polyphenylene sulfide composite materials in the existing technology still face performance deficiencies in practical applications, which limits their wider application; Most existing polyphenylene sulfide composite materials use glass fiber reinforcement to improve mechanical properties, but the interfacial bonding strength between glass fiber and matrix decreases rapidly at high temperatures, resulting in low high-temperature strength retention, which cannot meet the needs of long-term use under high-temperature conditions. In addition, due to the thermal expansion characteristics of the polyphenylene sulfide matrix itself, traditional single glass fiber reinforcement cannot effectively improve the dimensional stability of the material, and is prone to deformation under high-temperature conditions, affecting the accuracy and stability of the material; At the same time, polyphenylene sulfide materials are very brittle and prone to breakage under high load or impact conditions. Although existing modification methods such as elastomers or toughening agents have improved the performance, they often come at the expense of strength. In addition, although the introduction of nanofillers can significantly improve the thermal stability and mechanical properties of the material, the dispersion problem has not been effectively solved for a long time, and filler agglomeration has reduced the reinforcement efficiency. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a heat-resistant deformation engineering plastic and an air-conditioning fan blade, which solve the problems in the prior art of insufficient strength retention, poor dimensional stability and high brittleness of heat-resistant engineering plastics under high temperature conditions.

[0004] To achieve the above objectives, the present invention is implemented through the following technical scheme: a heat-resistant deformation engineering plastic, which includes the following components by weight percentage: 55% to 60% polyphenylene sulfide, 20% to 25% long glass fiber, 3% to 5% nano-silicon dioxide, 1% to 2% graphene filler, 8% to 10% benzoimide toughening agent, 0.5% to 1% cross-linking agent, and 0.2% to 0.5% antioxidant.

[0005] Preferably, the long glass fiber has a length of 8 to 12 mm and is surface treated with a 0.5% to 1% γ-APS silane coupling agent solution.

[0006] Preferably, the particle size of the nano-silicon dioxide is 20 to 40 nm, and the surface is activated by silane coupling agent KH-570 for 20 to 40 minutes.

[0007] Preferably, the graphene filler has a purity of ≥99%, has 1 to 3 layers, and has been subjected to ultrasonic dispersion treatment.

[0008] Preferably, the phenylimide toughening agent and polyphenylene sulfide are compatible-modified by grafting maleic anhydride with a polyphenylene sulfide compatibilizer.

[0009] The present invention also provides a method for preparing heat-resistant deformation engineering plastics, comprising the following steps: S1. Drying polyphenylene sulfide and surface activation of long glass fiber, nano-silicon dioxide and graphene; S2, mixing polyphenylene sulfide, long glass fiber, nano-silicon dioxide, graphene, phenylimide toughening agent, cross-linking agent and antioxidant according to weight percentage ratio; S3, melt blending is performed by a twin-screw extruder, the temperature is set to 280°C to 320°C, the screw speed is set to 100 to 120 rpm, and ultrasonic dispersion is used to assist the uniform distribution of the filler; S4, cooling the molten blended material to 80°C-100°C through a water cooling system, and pelletizing to form modified engineering plastic masterbatch.

[0010] Preferably, the surface activation treatment of the long glass fiber and nano-silicon dioxide is performed by using a silane coupling agent for activation, combined with ultrasonic dispersion auxiliary treatment, and the dispersion time is 30 minutes.

[0011] Preferably, during the melt blending process, the temperature is gradually increased in stages, and the temperature of each stage is set to 250°C to 270°C for the feeding stage, 280°C to 320°C for the melting stage, and 290°C to 310°C for the exhaust stage, so as to avoid thermal degradation of the raw materials and agglomeration of the fillers.

[0012] The invention also provides a heat-deformation-resistant air-conditioning fan blade, which is prepared from a heat-deformation-resistant engineering plastic.

[0013] Preferably, the preparation of the heat-resistant deformation air-conditioning fan blade includes: injection molding of engineering plastics by an injection molding machine, the barrel temperature is set to 290°C to 320°C, the mold temperature is set to, the holding time is 15 to 20 seconds, and during the injection molding process, the mold temperature is controlled to evenly drop to room temperature through a layer-by-layer cooling process.

[0014] The present invention provides a heat-resistant deformation-resistant engineering plastic and an air-conditioning fan blade, which have the following beneficial effects: 1. The present invention effectively enhances the rigidity and structural stability of the matrix by adding a variety of synergistic reinforcing components such as long glass fibers, nano-silicon dioxide and graphene to the polyphenylene sulfide matrix, especially maintaining a high strength retention rate under high temperature environment, solving the problem of decreased interfacial bonding strength of glass fiber reinforced materials at high temperatures in the prior art, and significantly improving the applicability of the material.

[0015] 2. The present invention forms a uniform microscopic enhanced network structure in the matrix by reasonably proportioning nano-silicon dioxide and graphene and adopting surface modification and ultrasonic dispersion technology, which effectively reduces the thermal expansion coefficient of the material, enables it to exhibit excellent dimensional stability in a high temperature environment, and avoids the deformation problem of existing materials caused by thermal expansion.

[0016] 3. The present invention modifies the polyphenylene sulfide matrix by using an imide toughening agent, thereby significantly improving the toughness of the material while maintaining the high strength characteristics of the material, solving the problem that the polyphenylene sulfide material is prone to fracture due to its high brittleness under high load conditions, and making the material have higher safety and reliability under complex working conditions.

[0017] 4. The present invention introduces the synergistic effect of nano-silicon dioxide and graphene, and combines the optimized design of the cross-linking agent and the antioxidant. The material of the present invention exhibits good thermal stability and antioxidant properties under high temperature environment, thereby extending the service life of the material under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart for preparing the heat-resistant deformation engineering plastic. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The embodiment of the present invention provides an engineering plastic resistant to heat deformation, which includes the following components in weight percentage: 55% to 60% of polyphenylene sulfide, 20% to 25% of long glass fiber, 3% to 5% of nano-silicon dioxide, 1% to 2% of graphene filler, 8% to 10% of phenylimide toughening agent, 0.5% to 1% of cross-linking agent, and 0.2% to 0.5% of antioxidant.

[0021] The length of the long glass fiber is 8-12 mm, and the surface of the long glass fiber is treated with 0.5%-1% γ-APS silane coupling agent solution.

[0022] The particle size of the nano silicon dioxide is 20-40 nm, and the surface is activated by silane coupling agent KH-570 for 20-40 minutes.

[0023] The purity of the graphene filler is ≥99%, the number of layers is 1 to 3, and the graphene filler is subjected to ultrasonic dispersion treatment.

[0024] The phenylimide toughening agent and polyphenylene sulfide are compatible and modified by grafting polyphenylene sulfide compatibilizer with maleic anhydride.

[0025] Specifically, polyphenylene sulfide is the base material of the present invention, and its molecular structure contains a large number of benzene rings and sulfide bonds, and has high thermal stability and good mechanical strength. It should be noted that the melting point of polyphenylene sulfide is about 280°C, and it can maintain excellent mechanical properties for a long time in an environment above 200°C, and is suitable as a structural material in high temperature conditions.

[0026] In a possible implementation, the selected polyphenylene sulfide is industrial grade high-purity particles with a melt index of 20 to 30 g / 10 min. The MFI in this range can ensure the fluidity of the material during extrusion and injection molding. In order to avoid degradation problems caused by moisture absorption during processing, the present invention performs vacuum drying on the polyphenylene sulfide particles, and the drying temperature is set to 150° C. for 6 to 8 hours.

[0027] It should be further pointed out that the bonding of polyphenylene sulfide with other reinforcing materials depends on the flow characteristics in the molten state. By controlling the ratio of polyphenylene sulfide matrix to filler, its heat resistance and dimensional stability can be optimized.

[0028] The long glass fiber is an important reinforcing phase of the present invention, and the continuous skeleton structure formed by the long glass fiber in the matrix significantly improves the bending strength and deformation resistance of the composite material.

[0029] Specifically, the length of the long glass fiber selected in the present invention is 8 to 12 mm. It should be noted that the selection of fiber length is closely related to the performance and processing characteristics of the composite material. Too long fibers may cause fiber breakage during processing, while too short fibers may reduce the reinforcement effect.

[0030] In one possible implementation, the surface of the glass fiber is treated with a 0.5% to 1% γ-APS silane coupling agent solution. The silane coupling agent reacts with the hydroxyl groups on the surface of the glass fiber to form a silanization layer. The chemical formula of the reaction is as follows: Si-OH+R-Si-(OEt)3→Si-O-Si-R+3EtOH The above surface modification can significantly improve the interfacial bonding strength between the glass fiber and the polyphenylene sulfide matrix. Exemplary treatment conditions are: immersing the glass fiber in a silane solution for 30 to 40 minutes, and then drying at 100° C. for 1 hour.

[0031] It should be pointed out that the bonding strength improvement effect after glass fiber surface treatment and its distribution uniformity jointly determine the mechanical properties of the final composite material.

[0032] Nano-silicon dioxide is used as a filler to reduce the linear thermal expansion coefficient of composite materials and improve their dimensional stability. Its particle size ranges from 20 to 40 nm. The smaller particle size enables it to be evenly dispersed in the matrix and provide significant filling and reinforcement effects.

[0033] In a possible implementation, nano-silicon dioxide is surface treated with a 0.5% silane coupling agent KH-570 solution. The specific steps include: Add nano-silicon dioxide to the silane coupling agent solution and mix them in a ratio of 1:5; Preliminary mixing under mechanical stirring conditions; The mixture was treated with ultrasonic dispersion (frequency 20-30 kHz) for 20-40 minutes to eliminate agglomeration, and then dried at 100° C. for 4 hours.

[0034] It should be noted that the surface modification of nano-silica enhances the bonding between the filler and the matrix through interfacial action, while improving the dispersion of the filler in the matrix, significantly improving the thermal stability of the composite material.

[0035] Graphene is a functional filler in the present invention, which can effectively improve the thermal conductivity of the composite material and the mechanical properties of the matrix through its high thermal conductivity and high specific surface area.

[0036] Specifically, the purity of graphene is ≥99%, the number of layers is 1 to 3, and its high specific surface area can promote the interface bonding with the substrate. At the same time, graphene is pre-treated by the following processes: Dispersing graphene in an ethanol solution with a concentration controlled at 0.5% to 1%; Treat in an ultrasonic device for 30 minutes (frequency 25kHz) to make it evenly dispersed; The drying temperature was set at 100°C for 4 hours.

[0037] It should be further pointed out that the dispersion uniformity of graphene is crucial to its enhancement effect. The present invention significantly improves the dispersion quality of graphene through an ultrasonic dispersion process.

[0038] The benzoimide toughening agent effectively improves the impact performance of the composite material by introducing flexible molecular segments, while avoiding the weakening effect of the reinforcing components on the toughness of the material.

[0039] In one possible implementation, the phenylimide toughening agent and polyphenylene sulfide are compatible-modified by a maleic anhydride grafting modifier, and this process connects the toughening agent and the polyphenylene sulfide molecular chain through a free radical reaction to form a highly compatible composite material.

[0040] The crosslinking agent (DCP, dicumyl peroxide) forms a three-dimensional molecular network structure through a free radical-initiated reaction, further improving the thermal stability and creep resistance of the composite material. The specific addition ratio is 0.5% to 1%. Excessive addition may cause excessive crosslinking, resulting in decreased processing performance.

[0041] Antioxidants (such as hindered phenol BHT) effectively extend the service life of materials by inhibiting the oxidative degradation of materials in high temperature environments. The specific addition ratio is 0.2% to 0.5%, which can ensure the antioxidant properties of the material without significantly affecting the fluidity of the matrix.

[0042] Please see attached Figure 1 The present invention also provides a method for preparing heat-resistant deformation engineering plastics, comprising the following steps: S1, drying polyphenylene sulfide, and surface activating long glass fibers, nano-silicon dioxide and graphene; S2, mixing polyphenylene sulfide, long glass fibers, nano-silicon dioxide, graphene, phenylimide toughening agent, cross-linking agent and antioxidant according to weight percentage ratio; S3, melt blending is performed by a twin-screw extruder, the temperature is set to 280°C to 320°C, the screw speed is set to 100 to 120 rpm, and ultrasonic dispersion is used to assist the uniform distribution of the filler; S4, cooling the molten blended material to 80°C-100°C through a water cooling system, and pelletizing to form modified engineering plastic masterbatch.

[0043] The surface activation treatment of the long glass fiber and nano-silicon dioxide is carried out by using a silane coupling agent for activation, combined with ultrasonic dispersion auxiliary treatment, and the dispersion time is 30 minutes.

[0044] During the melt blending process, the temperature is gradually increased in stages, with the temperatures of each stage set at 250°C to 270°C for the feeding stage, 280°C to 320°C for the melting stage, and 290°C to 310°C for the exhaust stage, to avoid thermal degradation of the raw materials and agglomeration of the fillers.

[0045] The heat-resistant deformation air-conditioning fan blade is made of heat-resistant deformation engineering plastic. The engineering plastic is injection molded by an injection molding machine. The barrel temperature is set to 290°C to 320°C, the mold temperature is set to, and the holding time is 15 to 20 seconds. During the injection molding process, the mold temperature is controlled to evenly drop to room temperature through a layer-by-layer cooling process.

[0046] Embodiment 1: In this embodiment, the formula and process parameters are selected within the range values ​​specified in the technical solution, which reflects the standardized implementation process of the present invention. The specific formula is as follows: Polyphenylene sulfide: 58%; Long glass fiber: 22%; Nano silicon dioxide: 4%; Graphene filler: 1.5%; Benzimide toughening agent: 9%; Cross-linking agent: 0.7%; Antioxidant: 0.3%.

[0047] The preparation method comprises the following steps: Step S1: The polyphenylene sulfide particles were placed in a vacuum drying oven at 150°C for 6 hours to remove moisture and prevent degradation or bubbling during processing; the long glass fiber was soaked in a 0.5% γ-APS silane coupling agent solution at room temperature for 30 minutes and then dried at 100°C for 1 hour. The silanization treatment enhanced the interfacial bonding between the glass fiber and the polyphenylene sulfide matrix; 4 parts of nano-SiO2 were added to a 0.5% KH-570 ethanol solution, ultrasonically dispersed (25kHz, 30 minutes), and then dried at 100°C for 4 hours; graphene was dispersed in a 0.5% ethanol solution, ultrasonically dispersed for 30 minutes, and then dried for use.

[0048] Step S2: Add all ingredients in proportion to a high-speed mixer and mix for 15 minutes to ensure a uniform mixture.

[0049] Step S3: A twin-screw extruder was used for melt blending, and the process parameters were set as follows: Feed section temperature: 260°C; Melting temperature: 300℃; Exhaust section temperature: 310℃; Screw speed: 110rpm; At the same time, combined with ultrasonic assisted dispersion technology (frequency 25kHz), the uniform distribution of the filler is improved. The ultrasonic transducer is installed on the wall of the melting section or in the melting cavity of the twin-screw extruder to directly transmit the ultrasonic energy to the high-viscosity polymer melt and filler mixture.

[0050] Step S4: The melt was cooled in a 90°C cooling water tank for 20 seconds and then pelletized to obtain engineering plastics.

[0051] Embodiment 2: The specific formula is as follows: Polyphenylene sulfide: 54%; Long glass fiber: 19%; Nano silicon dioxide: 2.5%; Graphene filler: 0.8%; Benzimide toughening agent: 7%; Cross-linking agent: 0.4%; Antioxidant: 0.2%.

[0052] The preparation method comprises the following steps: Step S1: Lowering the drying temperature of polyphenylene sulfide particles to 140°C and shortening the drying time to 4 hours may result in a slightly higher moisture content; glass fiber surface treatment: the concentration of γ-APS solution was reduced to 0.4%, the immersion time was 20 minutes, and the drying temperature was still 100°C; nano-silica activation: the activation treatment time was shortened to 20 minutes; graphene dispersion: no ultrasonic dispersion treatment was performed, only mechanical stirring and mixing.

[0053] Step S2: The mixing time was reduced to 10 minutes.

[0054] Step S3: A twin-screw extruder was used for melt blending, and the process parameters were set as follows: Feed section temperature: 250℃; Melting temperature: 280℃; Exhaust section temperature: 290℃; Screw speed: 100rpm; Ultrasonication-assisted dispersion technology was not used.

[0055] Step S4: The cooling water temperature is lowered to 85°C and pelletized after cooling for 10 seconds.

[0056] Embodiment 3: The specific formula is as follows: Polyphenylene sulfide: 60%; Long glass fiber: 25%; Nano silicon dioxide: 5%; Graphene filler: 2%; Benzimide toughening agent: 10%; Cross-linking agent: 1%; Antioxidant: 0.5%.

[0057] The preparation method comprises the following steps: Step S1: The drying temperature of polyphenylene sulfide particles was increased to 160°C and the time was extended to 8 hours. When treating the glass fiber surface, the concentration of γ-APS solution was increased to 1%, the immersion time was extended to 40 minutes, and the drying temperature was still 100°C. The activation treatment time of nano-silica was extended to 40 minutes, and high-power ultrasonic dispersion (30kHz) was used. When dispersing graphene, the ultrasonic dispersion time was extended to 40 minutes.

[0058] Step S2: Mixing time extended to 20 minutes Step S3: A twin-screw extruder was used for melt blending, and the process parameters were set as follows: Feed section temperature: 270°C; Melting temperature: 320℃; Exhaust section temperature: 310℃; Screw speed: 120rpm; The ultrasonic dispersion frequency was increased to 30 kHz.

[0059] Step S4: The cooling water temperature was raised to 100°C and the cooling time was extended to 30 seconds.

[0060] Summary: In Example 1, under reasonable proportions and process conditions, the material performance is balanced, and can achieve an optimal balance between mechanical properties, thermal stability and processability. It can be widely used in high temperature and high load scenarios, such as air conditioning fan blades and other structural parts.

[0061] In Example 2, the component ratio is reduced in Example 1, so that the processing fluidity of the material is better, the melt blending process is more stable, the processing difficulty is reduced, and it is suitable for low-end or mid-end application needs of mass production.

[0062] Example 3 increases the component ratio based on Example 1 and Example 2, and its high performance is very suitable for high-temperature and high-load application scenarios, such as heat-resistant parts in industrial equipment, automobile engine hoods, air-conditioning fan blades, and load-bearing parts that need to run at high temperatures for a long time.

[0063] Each embodiment not only improves the heat deformation resistance of engineering plastics, but also achieves the best balance between performance, cost and process operation within the range of component ratios and process parameters.

[0064] 1. Design comparative experiment 1 to verify the advantages of bending strength retention and dimensional stability of air-conditioning fan blades made of heat-resistant deformation-resistant engineering plastics compared with existing technologies.

[0065] 2. Experimental purpose: This experiment aims to verify the significant advantages of the bending strength retention rate and dimensional stability of the heat-resistant deformation engineering plastic material of the present invention under high temperature conditions compared with the prior art, and to analyze the performance differences of materials in different embodiments, focusing on: Nanofillers improve dimensional stability and strength retention at high temperatures; The performance gap between the material of the present invention and the prior art; The changes in performance of materials in different embodiments and their reasons.

[0066] 3. Preparation of experimental materials: Comparative sample 1 (prior art sample): Material composition: Single glass fiber reinforced polyphenylene sulfide, glass fiber content 22%, no nano-SiO2, graphene or toughening agent.

[0067] Example 1 Materials: Material composition: the material of the present invention with a standard range value ratio, 58% of polyphenylene sulfide, 22% of glass fiber, 24% of nano-SiO, 1.5% of graphene, 9% of benzoimide toughening agent, 0.7% of cross-linking agent, and 0.3% of antioxidant.

[0068] Example 2 Materials: Material composition: the material of the present invention with a ratio below the range value, 54% of polyphenylene sulfide, 19% of glass fiber, 2.5% of nano-SiO2, 0.8% of graphene, 7% of benzoimide toughening agent, 0.4% of cross-linking agent, and 0.2% of antioxidant.

[0069] Example 3 Materials: Material composition: the material of the present invention with a ratio higher than the range value, 60% of polyphenylene sulfide, 25% of glass fiber, 25% of nano-SiO, 2% of graphene, 10% of benzoimide toughening agent, 1% of cross-linking agent, and 0.5% of antioxidant.

[0070] 4. Specific experimental process: The air-conditioning fan blade samples were prepared using the injection molding process. The sample diameter was 200 mm and the thickness was 2 mm to ensure that the geometric dimensions of each sample were consistent.

[0071] All materials were melt blended in a twin-screw extruder according to the ratio, and a unified processing technology was adopted (temperature 280° C. to 310° C., screw speed 110 rpm, water-cooled pelletizing).

[0072] All samples were dried at 120 °C for 4 h before injection molding to ensure that the moisture in the material was completely removed to avoid bubbles or abnormal performance during processing.

[0073] Experimental steps: Step 1: Bending strength retention test under high temperature environment: Equipment preparation: A three-point bending strength testing machine was used, the test standard was ISO178, the span was 64 mm, and the loading speed was 2 mm / min.

[0074] Experimental conditions: The samples were placed in high temperature environments of 180°C and 200°C for 100 hours respectively to simulate the long-term high temperature conditions in air-conditioning operation.

[0075] Test method: After standing, take out the sample and immediately test its flexural strength. Compare it with the initial flexural strength and calculate the flexural strength retention rate (%). The formula is as follows: Step 2: High temperature dimensional stability test: Equipment preparation: The diameter change of the sample was measured using a high-precision caliper (accuracy ± 0.01 mm).

[0076] Experimental conditions: The samples were placed in high temperature environments of 180°C and 200°C for 100 hours, respectively, and the diameter changes before and after standing were recorded.

[0077] Test method: Measure the diameter change of the sample after standing at high temperature, and calculate the size change rate (%). The formula is as follows: 5. Experimental data record: Bending strength retention rate: Dimensional change rate: Data analysis summary: Bending strength retention analysis: Comparative sample 1: At 180℃ and 200℃, the flexural strength drops rapidly, with the retention rates being only 60% and 40% respectively, indicating that the single glass fiber reinforced polyphenylene sulfide material cannot maintain sufficient strength at high temperatures. This is because the glass fiber only provides mechanical support under high temperature conditions and lacks the effect of enhancing the thermal stability of the matrix.

[0078] Example 2 Materials: At 180°C and 200°C, the flexural strength retention rates were 75% and 65% respectively, which were significantly improved compared with the comparative sample 1. This is because the introduction of a small amount of nano-silica and graphene fillers improved the high-temperature performance of the matrix to a certain extent.

[0079] Example 1 Materials: The flexural strength retention rates are 90% and 85% respectively, which are significantly better than those of Example 2 and Comparative Sample 1. This is because the contents of nanofillers and glass fibers have reached the optimal ratio range, forming a good microscopic reinforcement network under high temperature environment and enhancing the interfacial bonding force of glass fibers.

[0080] Example 3 Materials: The flexural strength retention rates are 92% and 90% respectively, showing the best performance. This is because the higher content of nano-silica and graphene further reduces the thermal expansion coefficient of the matrix and enhances the high-temperature rigidity.

[0081] Dimensional change rate analysis: Comparative sample 1 (prior art): At 180℃ and 200℃, the dimensional change rates are 1.5% and 2.0% respectively, indicating that the thermal expansion coefficient of the material is high at high temperatures and the dimensional stability is poor. This is because the mechanical reinforcement of glass fiber cannot significantly improve the dimensional stability due to the lack of nanofiller's constraint on the matrix.

[0082] Example 2 Materials: The dimensional change rates are 0.8% and 1.2%, respectively, which are significantly lower than those of comparative sample 1. This is because the addition of a small amount of nanofillers reduces the thermal expansion coefficient of the matrix to a certain extent.

[0083] Example 1 Materials: The dimensional change rates are 0.2% and 0.5%, respectively, showing excellent dimensional stability. This is because the synergistic effect of nanofillers and graphene forms a uniform reinforcement network, which significantly suppresses thermal expansion.

[0084] Example 3 Materials: The dimensional change rate is further reduced to 0.15% and 0.2%, showing the best dimensional stability. This is because the higher content of nanofillers forms a denser microstructure in the matrix, which has a stronger constraint on the thermal expansion of the matrix.

[0085] VI. Conclusion By comparing Experiment 1, we can draw the following conclusions: Deficiencies of existing technology: Comparative sample 1 (single glass fiber reinforced polyphenylene sulfide) suffers from a serious drop in strength at high temperatures and a high rate of dimensional change, which cannot meet the requirements of high temperature working conditions.

[0086] Improvement of Example 2: Although the component ratio is low, the high-temperature performance of the material is improved to a certain extent through the synergistic effect of a small amount of nanofillers and glass fibers, making it suitable for low- and mid-end scenarios.

[0087] Performance balance of Example 1: By optimizing the ratio and process, the material achieves the best balance between performance and economy in terms of high temperature strength retention and dimensional stability.

[0088] The performance of Example 3 is the best: the high content of nanofillers and graphene significantly improves the high-temperature performance of the material, but increases the processing complexity and cost, and is suitable for high-end application scenarios.

[0089] In summary: the embodiments of the present invention achieve significant high-temperature strength retention and dimensional stability through the introduction and reasonable proportion of nanofillers, especially Examples 1 and 3 show excellent mechanical properties and thermal stability in a high-temperature environment of 200°C, which greatly surpasses the single glass fiber reinforced PPS material in the prior art.

[0090] 1. Design comparative experiment 2 to verify the advantages of bending strength and impact strength of air-conditioning fan blades made of heat-resistant deformation-resistant engineering plastics over existing technologies.

[0091] 2. Experimental purpose: The purpose of this experiment is to verify the effect of surface treatment of glass fiber on improving the interfacial bonding strength of the matrix and its significant influence on the material reinforcement efficiency. By comparing the prior art with the present invention, the bending strength and impact strength of the material are tested at room temperature and high temperature, and the influence of different treatment methods and component ratios is analyzed.

[0092] Specific goals include: Verify the effect of silane coupling agent treatment on improving the interfacial bonding strength between glass fiber and matrix; Compare the enhancement efficiency of materials from different embodiments, and analyze the effects of ratio and surface treatment optimization on performance; Study the effect of interfacial bonding force on maintaining material enhancement properties under high temperature conditions.

[0093] 3. Experimental Materials Comparative sample 2 (prior art sample): Material composition: glass fiber not treated with silane coupling agent (glass fiber content 22%), and other components are consistent with Example 1.

[0094] Example 1 Materials: Material composition: the material of the present invention with a standard ratio, 58% polyphenylene sulfide, 22% glass fiber, 4% nanometer, 1.5% graphene, 9% benzoimide toughening agent, the glass fiber is treated with 0.5% γ-APS silane solution, and the treatment time is 30 minutes.

[0095] Example 2 Materials: Material composition: the material of the present invention with a ratio below the range value, 54% polyphenylene sulfide, 19% glass fiber, 2.5% nano, 0.8% graphene, 7% benzoimide toughening agent, the glass fiber is treated with a low concentration (0.3%) γ-APS silane solution, and the treatment time is 20 minutes.

[0096] Example 3 Materials: Material composition: The material of the present invention with a ratio higher than the range value, 60% polyphenylene sulfide, 25% glass fiber, 5% nano, 2% graphene, 10% phenylimide toughening agent, the glass fiber is treated with a high concentration (1%) γ-APS silane solution, and the treatment time is 40 minutes.

[0097] 4. Specific experimental process: Sample preparation: Material Mixing: The materials were mixed in a high-speed mixer for 10 minutes according to the proportions to ensure uniform distribution.

[0098] A twin-screw extruder was used for melt blending (processing temperature 250-310° C., screw speed 110 rpm), and pelletization was performed to obtain a modified material.

[0099] Fiberglass surface treatment: Comparative sample 2: The glass fiber is directly added to the matrix without any treatment.

[0100] Example 1, Example 1, Example 3 Materials: Glass fibers were soaked in γ-APS silane solutions of different concentrations (20 to 40 minutes) and then dried (100° C., 1 hour).

[0101] Sample molding: The test samples were prepared using an injection molding machine with dimensions of (80 mm×10 mm×4 mm).

[0102] Test steps: Step 1: Bending strength test: Equipment and standards: A three-point bending tester was used in accordance with ISO178 standard, with a span of 64 mm and a loading speed of 2 mm / min.

[0103] Test environment: The flexural strength of the samples was tested at room temperature (25°C) and at a high temperature of 200°C.

[0104] Data processing: The flexural strength was recorded and compared with a control sample.

[0105] Step 2: Impact strength test: Equipment and standards: The impact strength of the samples was tested using a simply supported beam impact tester in accordance with ISO179 standard.

[0106] Test environment: Impact tests were performed at room temperature (25°C) and at a high temperature of 200°C.

[0107] 5. Experimental data record: Experimental data analysis: Comparative sample 2 (prior art sample): Flexural strength: The flexural strength at room temperature and 200°C is 180MPa and 140MPa respectively, which is poor. This is because the interface bonding between the untreated glass fiber and the matrix is ​​poor, and it is easy to separate from the matrix after loading, resulting in low reinforcement efficiency.

[0108] Impact strength: Impact strength is 11.0kJ / m 2 (room temperature) and 8.5 kJ / m 2 (200℃), showing greater brittleness.

[0109] Example 2 Materials: Flexural strength: After the glass fiber is treated with low-concentration γ-APS, the interfacial bonding strength is improved, and the flexural strength is increased to 200MPa and 170MPa at room temperature and 200°C, respectively, which is a significant improvement over the comparative sample 1.

[0110] Impact strength: The impact strength is 13.5kJ / m 2 (room temperature) and 10.0 kJ / m 2 (200℃), the toughness is slightly improved.

[0111] Example 1 Materials: Flexural strength: Through optimized glass fiber surface treatment (0.5% silane solution), the flexural strength is further improved to 220MPa and 200MPa at room temperature and high temperature, showing excellent reinforcement efficiency.

[0112] Impact strength: The impact strength is 16.0kJ / m 2 (room temperature) and 12.0 kJ / m 2 (200℃), showing good toughness and high temperature performance.

[0113] Example 3 Materials: Flexural strength: The glass fiber treated with high-concentration silane solution has the strongest interfacial bonding strength, with flexural strength reaching 225MPa and 215MPa at room temperature and 200°C respectively, with optimal performance.

[0114] Impact strength: The impact strength is 17.5kJ / m 2 (room temperature) and 14.0 kJ / m 2 (200℃), showing the highest toughness and high temperature performance.

[0115] VI. Conclusion Insufficient existing technology: Since the glass fiber of comparative sample 2 has not been surface treated, the bonding strength with the matrix is ​​poor, resulting in low reinforcement efficiency, and poor bending strength and impact strength at room temperature and high temperature conditions.

[0116] The present invention treats the glass fiber surface by using a silane coupling agent, thereby significantly improving the interface bonding force, thereby improving the bending resistance and impact strength.

[0117] Examples 1 and 3 combine appropriate silane solution concentration and treatment time, and show higher enhancement efficiency, especially in high temperature environments.

[0118] Performance and cost balance: The material of Example 1 achieves the best balance between enhanced efficiency and processing economy and is suitable for a wide range of applications; the material of Example 2 is significantly improved over the comparative sample 1 and is suitable for the bottom-end application market; the material of Example 3 has the best performance but a higher processing cost and is more suitable for high-end application scenarios.

[0119] In summary: through the optimized treatment of the glass fiber surface by silane coupling agent, the embodiments of the present invention significantly improve the interfacial bonding force between the glass fiber and the matrix, enhance the bending strength and impact toughness of the material, especially under high temperature conditions, the reinforcement efficiency of Examples 1 and 3 is much better than that of untreated glass fiber.

[0120] 1. Design comparative experiment 3 to verify the dimensional change rate and thermal expansion coefficient of air-conditioning fan blades made of heat-resistant deformation engineering plastics under high temperature conditions compared with the existing technology.

[0121] 2. Experimental purpose: This experiment aims to verify the key role of nanofiller (nano-silica and graphene) dispersion in the thermal stability and dimensional stability of heat-resistant deformation engineering plastics. By comparing fillers that have not been dispersed and fillers that have been dispersed by ultrasonic waves (example materials), the dimensional change rate and thermal expansion coefficient (CTE) under high temperature conditions are tested to clarify the importance of dispersion technology in modified engineering plastics. The specific goals include: Analyze the performance difference in thermal stability between the filler without dispersion treatment (comparative sample 1) and the filler with ultrasonic dispersion treatment (example material); Compare the effects of dispersion degree on dimensional stability and thermal expansion coefficient in different example materials; Explore how the agglomeration of nanofillers affects the performance of materials.

[0122] 3. Experimental Materials Comparative sample 3 (prior art sample): Material composition: nano silicon dioxide and graphene without dispersion treatment (the other components are consistent with Example 1).

[0123] Example 1 Materials: Material composition: standard ratio material of the present invention, 58% polyphenylene sulfide, 22% glass fiber, 24% nano-SiO, 1.5% graphene, 9% benzoimide toughening agent, 0.7% cross-linking agent, 0.3% antioxidant, treated by ultrasonic dispersion (25kHz, 30 minutes).

[0124] Example 2 Materials: Material composition: low-ratio material of the present invention, material of the present invention with a ratio below the range value, 54% polyphenylene sulfide, 19% glass fiber, 2.5% nano, 0.8% graphene, 7% benzoimide toughening agent, 0.4% cross-linking agent, 0.2% antioxidant, treated with ultrasonic dispersion (20kHz, 20 minutes).

[0125] Example 3 Materials: Material composition: the high-ratio material of the present invention comprises 60% polyphenylene sulfide, 25% long glass fiber, 5% nano-silicon dioxide, 2% graphene filler, 10% benzoimide toughening agent, 1% cross-linking agent, and 0.5% antioxidant (BHT), and is treated by ultrasonic dispersion (30kHz, 40 minutes).

[0126] 4. Specific experimental process Sample preparation: Filler pretreatment: Comparative sample 3: The nanofiller was directly mixed into the PPS matrix without additional treatment.

[0127] Example 1, Example 2, Example 3 Materials: Nano-silicon dioxide and graphene are dispersed in 0.5% silane coupling agent solution, respectively, and ultrasonic equipment is used to perform dispersion treatment at different powers and times, and then dried for use.

[0128] Material mixing and processing: Add all ingredients according to the proportions into a high-speed mixer and mix for 10 minutes.

[0129] The modified material was prepared by melt blending and pelletizing using a twin-screw extruder (processing temperature 250-310° C., screw speed 110 rpm).

[0130] Sample molding: Test specimens (80 mm×10 mm×4 mm) were prepared by injection molding.

[0131] Test steps: Step 1: High temperature dimensional change rate test: Equipment and standards: A high-precision caliper (accuracy ±0.01 mm) was used to measure the dimensional change rate of the sample under high temperature environment.

[0132] Experimental conditions: The samples were placed in a high temperature environment of 200°C for 100 hours.

[0133] Test method: Record the length change of the sample before and after standing, and calculate the dimensional change rate (%). The formula is as follows: Step 2: Thermal Expansion Coefficient Test: Equipment and standards: The coefficient of linear thermal expansion (CTE) of the samples was tested using a thermomechanical analyzer (TMA) according to ASTM E831 standard.

[0134] Experimental conditions: Temperature range: 30℃ to 200℃, heating rate: 10℃ / min.

[0135] Test method: Record the thermal expansion behavior of the sample at different temperatures and calculate the linear thermal expansion coefficient using the following formula: Where ΔL is the length change of the sample, L0 is the initial length, and ΔT is the temperature change range.

[0136] 5. Experimental data record: Experimental data analysis: Comparative sample 3 (prior art sample): Dimensional change rate: 1.2%, thermal expansion coefficient is 80×10 -6 / K, showing significant dimensional instability.

[0137] Cause analysis: Due to the lack of dispersion treatment, the nanofillers are easily agglomerated in the matrix and fail to form a uniform reinforcement network, resulting in no improvement in the thermal expansion behavior and dimensional stability of the material.

[0138] Example 2 Materials: Dimensional change rate: 0.8%, thermal expansion coefficient is 65×10 -6 / K, which is significantly improved compared with comparative sample 1.

[0139] Cause analysis: Although the dispersion treatment time is short, it still partially alleviates the filler agglomeration phenomenon and improves the thermal expansion performance, but due to incomplete dispersion, the reinforcement effect is limited.

[0140] Example 1 Materials: Dimensional change rate: 0.2%, thermal expansion coefficient is 45×10 -6 / K, showing excellent dimensional stability.

[0141] Cause analysis: The optimized ultrasonic dispersion technology (25kHz, 30 minutes) significantly improved the uniformity of the nanofillers, formed a continuous microscopic reinforcement network in the matrix, and greatly reduced the thermal expansion behavior of the material.

[0142] Example 3 Materials: Dimensional change rate: 0.15%, thermal expansion coefficient is 40×10 -6 / K, best performance.

[0143] Cause analysis: Higher power and longer ultrasonic dispersion further improve the uniformity of filler distribution and make the network denser, thus achieving the highest level of dimensional stability and thermal expansion performance.

[0144] VI. Conclusion Insufficient existing technology: Comparative sample 3 had serious filler agglomeration problems and failed to improve the thermal expansion behavior of the matrix, resulting in a large high-temperature dimensional change rate and a high thermal expansion coefficient.

[0145] Improvements of the present invention: In Example 2, the filler agglomeration phenomenon is reduced to a certain extent through a short period of ultrasonic dispersion treatment, thereby improving the thermal stability and dimensional stability of the material.

[0146] In Example 1 and Example 3, the nanofillers are evenly distributed by optimized ultrasonic dispersion technology to form a continuous reinforcement network, thereby significantly improving the high temperature performance.

[0147] Performance and processing balance: Example 1 achieves an optimal balance between material performance and processing economy and is suitable for practical application scenarios.

[0148] The material performance of Example 3 is the best, but the dispersion technology requirements are relatively high and it is suitable for high-end applications.

[0149] In summary: The embodiments of the present invention solve the problem of nanofiller agglomeration through ultrasonic dispersion technology, form a uniform microscopic reinforced network, significantly reduce the thermal expansion coefficient of the material, and improve the dimensional stability and thermal stability. In particular, the performance of Embodiments 1 and 3 is the most outstanding.

[0150] The present invention provides a heat-resistant deformation engineering plastic, which uses polyphenylene sulfide as a matrix, adds a variety of reinforcing fillers such as long glass fiber, nano-silica and graphene, as well as phenylimide toughening agents and cross-linking agents for synergistic modification, and combines silane treatment on the surface of glass fiber, ultrasonic dispersion technology and optimized melt blending process, effectively solving the problems of insufficient high-temperature strength, poor dimensional stability and low toughness in the prior art. The material of the present invention exhibits excellent mechanical properties, thermal stability and dimensional stability under a high temperature environment of 200°C, significantly improving the scope of application of the product, and is widely used in the fields of air-conditioning fan blades, high-temperature industrial components, etc., while taking into account the best balance of processing economy and performance.

[0151] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A heat-resistant deformation engineering plastic, characterized in that: Calculated by weight percentage, it includes the following components: 55% to 60% polyphenylene sulfide, 20% to 25% long glass fiber, 3% to 5% nano-silicon dioxide, 1% to 2% graphene filler, 8% to 10% phenylimide toughening agent, 0.5% to 1% cross-linking agent, and 0.2% to 0.5% antioxidant.

2. The heat-deformation-resistant engineering plastic according to claim 1, characterized in that: The long glass fiber has a length of 8 to 12 mm and is surface treated with a 0.5% to 1% γ-APS silane coupling agent solution.

3. The heat-deformation-resistant engineering plastic according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 20-40 nm, and the surface is activated by silane coupling agent KH-570 for 20-40 minutes.

4. The heat-deformation-resistant engineering plastic according to claim 1, characterized in that: The graphene filler has a purity of ≥99%, has 1 to 3 layers, and is subjected to ultrasonic dispersion treatment.

5. The heat-deformation-resistant engineering plastic according to claim 1, characterized in that: The benzimide toughening agent and polyphenylene sulfide are compatible-modified by grafting a polyphenylene sulfide compatibilizer with maleic anhydride.

6. A method for preparing heat-resistant deformation engineering plastics, characterized in that: A heat-deformation-resistant engineering plastic according to any one of claims 1 to 5, comprising the following steps: S1. Drying polyphenylene sulfide and surface activation of long glass fiber, nano-silicon dioxide and graphene; S2, mixing polyphenylene sulfide, long glass fiber, nano-silicon dioxide, graphene, phenylimide toughening agent, cross-linking agent and antioxidant according to weight percentage ratio; S3, melt blending is performed by a twin-screw extruder, the temperature is set to 280°C to 320°C, the screw speed is set to 100 to 120 rpm, and ultrasonic dispersion is used to assist the uniform distribution of the filler; S4, cooling the molten blended material to 80°C-100°C through a water cooling system, and pelletizing to form modified engineering plastic masterbatch.

7. The method for preparing heat-resistant deformation-resistant engineering plastics according to claim 6, characterized in that: The surface activation treatment of the long glass fiber and nano-silicon dioxide adopts silane coupling agent for activation, combined with ultrasonic dispersion auxiliary treatment, and the dispersion time is 30 minutes.

8. The method for preparing heat-resistant deformation-resistant engineering plastics according to claim 6, characterized in that: During the melt blending process, the temperature is gradually increased in stages, and the temperature of each stage is set to 250°C to 270°C for the feeding stage, 280°C to 320°C for the melting stage, and 290°C to 310°C for the exhaust stage, so as to avoid thermal degradation of the raw materials and agglomeration of the fillers.

9. A heat-resistant deformation air-conditioning fan blade, characterized in that: The air conditioner fan blade is made of a heat-resistant deformation-resistant engineering plastic as described in any one of claims 1-5.

10. The heat-resistant deformation air-conditioning fan blade according to claim 9, characterized in that: The preparation of the heat-resistant deformation air-conditioning fan blade includes: the engineering plastic is injection molded by an injection molding machine, the barrel temperature is set to 290°C to 320°C, the mold temperature is set to, and the holding time is 15 to 20 seconds. During the injection molding process, the mold temperature is controlled to evenly drop to room temperature through a layer-by-layer cooling process.

Citation Information

Patent Citations

  • Polyphenylene sulfide composite material, preparation method and molding method thereof

    CN103224706A

  • High-toughness wear-resistant polyphenylene sulfide composite material

    CN110643179A

  • Polyphenylene sulfide composite material and preparation method thereof

    CN113025039A

  • Long-fiber reinforced thermoplastic resin composition with excellent thermal conductivity and mechanical properties

    KR1020160083519A

Cited By

  • Nano modified polyformaldehyde plastic particle

    CN120484433A

  • Nanomodified polyoxymethylene plastic particles

    CN120484433B